Presuppositions and discourse : essays offered to Hans Kamp - Bäuerle, Rainer; Reyle, U., 1955-; Zimmermann, Thomas Ede, 1954- (Current research in the semantics/pragmatics interface, 2010)
Undoubtedly, presupposition theory is a major chapter in the success story of dynamic semantics. This book features papers on this topic based on a conference on ""Presupposition"" convened in Stuttgart in October 2000.